Development of Physical Education Textbook Based on Direct Instructions for Children with Special Needs - Alchonity Harika Fitri; Lukman Firnando Putra (Universitas PGRI Palembang, 2022)
Special children who are called children with special needs (ABK), their privileges become the background of the problems in this study, where there is still a lack of variety in physical education learning for children with special needs, and there is no textbook that specifically presents physical education learning according to the characteristics of ABK. Based on the problems and needs analysis, the researchers developed textbooks as a solution to solving problems in the field. Physical education textbooks based on direct instruction for ABK, aim to facilitate teachers in providing physical education learning in accordance with the characteristics of ABK that are valid, practical and effective. This research was researched using the Research and Development (R&D) 4D model (Define, Design, Develop, Dessiminate). The subjects of the research trial were students of SLBN 1 Pulau Punjung, SLB Koto Agung, and SLB Attallah Dharmasraya at the elementary school (SD) level. The data collection instruments used were validation sheets, practicalization sheets, effectiveness sheets from the test results for the characteristics of physical education subjects. Based on the research that has been carried out, the results of the validity test have an average value of 82.12% with a very valid category, for the practicality test an average of 80% is obtained with the practical category and the effectiveness test, an average of 75% with the medium category. Therefore, it can be concluded that direct instruction-based physical education textbooks for children with special needs can be used in physical education subjects with valid, practical and effective categories.